Obesity and its Relationship with Covid-19: A Review of the Main Pharmaceutical Aspects - Hodel, Katharine; Fonseca, Ananda; Barbosa, Islania; Medina, Caio; Alves, Brenda; Maciel, Carine; Nascimento, Daniel; Oliveira-Junior, Gessualdo; Pedreira, Lorena; de Souza, Monielly; Godoy, Ana Leonor (Current Pharmaceutical Biotechnology, 2024)
Important physiological changes are observed in patients with obesity, such as intestinal permeability, gastric emptying, cardiac output, and hepatic and renal function. These differences can determine variations in the pharmacokinetics of different drugs and can generate different concentrations at the site of action, which can lead to sub therapeutic or toxic concentrations. Understanding the physiological and immunological processes that lead to the clinical manifestations of COVID-19 is essential to correlate obesity as a risk factor for increasing the prevalence, severity, and lethality of the disease. Several drugs have been suggested to control COVID- 19 like Lopinavir, Ritonavir, Ribavirin, Sofosbuvir, Remdesivir, Oseltamivir, Oseltamivir phosphate, Oseltamivir carboxylate, Hydroxychloroquine, Chloroquine, Azithromycin, Teicoplanin, Tocilizumab, Anakinra, Methylprednisolone, Prednisolone, Ciclesonide and Ivermectin. Similarly, these differences between healthy people and obese people can be correlated to mechanical factors, such as insufficient doses of the vaccine for high body mass, impairing the absorption and distribution of the vaccine that will be lower than desired or can be linked to the inflammatory state in obese patients, which can influence the humoral immune response. Additionally, different aspects make the obese population more prone to persistent symptoms of the disease (long COVID), which makes understanding these mechanisms fundamental to addressing the implications of the disease. Thus, this review provides an overview of the relationship between COVID-19 and obesity, considering aspects related to pharmacokinetics, immunosuppression, immunization, and possible implications of long COVID in these individuals.
Keywords: SARS-CoV-2